2012
DOI: 10.3390/molecules17044047
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Fluorescence Microscopy Techniques—FRAP, FLIP, FLAP, FRET and FLIM

Abstract: Fluorescence microscopy provides an efficient and unique approach to study fixed and living cells because of its versatility, specificity, and high sensitivity. Fluorescence microscopes can both detect the fluorescence emitted from labeled molecules in biological samples as images or photometric data from which intensities and emission spectra can be deduced. By exploiting the characteristics of fluorescence, various techniques have been developed that enable the visualization and analysis of complex dynamic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
359
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(366 citation statements)
references
References 298 publications
(392 reference statements)
3
359
0
4
Order By: Relevance
“…Subsequently, the binding of glucose to GBP induces a conformational change which may apparently bring closer both these two fluorescent proteins and therefore there is an increase in FRET efficiency. Several research workers have reported that FRET is apparently a very complex process when free and immobilized whole-cells or cell-free extracts are involved [19][20][21][22]. Regarding the differences in FRET efficiencies between the free and immobilized nanosensors, there are a number of factors affecting immobilized and soluble proteins such as restricted mobility on immobilization, chemical modification due to the immobilization method used, nature of the microenvironment and diffusion limitation [20].…”
Section: Glucose Assaymentioning
confidence: 99%
“…Subsequently, the binding of glucose to GBP induces a conformational change which may apparently bring closer both these two fluorescent proteins and therefore there is an increase in FRET efficiency. Several research workers have reported that FRET is apparently a very complex process when free and immobilized whole-cells or cell-free extracts are involved [19][20][21][22]. Regarding the differences in FRET efficiencies between the free and immobilized nanosensors, there are a number of factors affecting immobilized and soluble proteins such as restricted mobility on immobilization, chemical modification due to the immobilization method used, nature of the microenvironment and diffusion limitation [20].…”
Section: Glucose Assaymentioning
confidence: 99%
“…1 Chip-based biomolecular analysis methods, such as DNA chips and protein chips, are also based on fluorescence imaging. The quality of fluorescence imaging and the sensitivity of fluorescence detection are generally evaluated by the signal-to-noise (S/N) ratio, which indicates the ratio between the fluorescence signal from a fluorophore and the background light.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid progress of modern life science depends to a large extent on the use of advanced imaging techniques [1,2]. In particular, the design of fluorescent markers that can be genetically encoded and expressed in vivo have enormously contributed to our understanding of subcellular processes.…”
Section: Introductionmentioning
confidence: 99%